The accuracy of slope images derived from GIS software - Ibrahim, Norkhair (Faculty of Geoinformation Science and Engineering, 2003)
A major part of high frequency gravity signals is governed by the masses of topography. Practically, this effect can be evaluated by using the integration formula of terrain corrections. In this study, the topographic conditions are classified as: Block I (flat), Block II (hilly), and Block III (mountainous). The analysis of the results indicated that the terrain effects are very significant for gravity field information in rough terrains compared to relatively flat areas. A denser grid spacing of Digital Elevation Model (DEM) would contain a lot of gravitational features, especially in the rough terrains. In contrast, for the flat areas, the effect of topographic masses is insignificant, resulting in very small magnitudes as would be expected.